Effect of Reflective Instructional Strategy on Secondary School Students’ Achievement in Chemistry in Awka Education Zone, Anambra State - Agbasi, O. S.; Okeke, S. O. C. (UNIZIK Journal of STM Education, 2020)
The strategy used in teaching chemistry to students is one of the determining factors towards their achievement. Thus the study investigated the effect of reflective instructional strategy (RIS) on secondary school students’ achievement in chemistry. Two research questions guided the study and two hypotheses were tested at 0.05 level of significance. A quasi experimental design, specifically pre-test post-test non-equivalent control group design was adopted for the study. The population of the study was 2,474 senior secondary class two (SS2) chemistry students. A total of 165 SS2 chemistry students from four co-educational schools in Awka Education Zone of Anambra state were involved in the study. Simple random sampling was used to select four schools from the 46 co-educational schools in the zone. The four schools were randomly assigned, two schools respectively were assigned to the experimental and control groups. Chemistry Achievement Test (CAT) was used for data collection. The instrument was validated by three experts. The internal consistency of the CAT was established using KR-20. The reliability coefficient of 0.83 was obtained. Two regular chemistry teachers in each of the schools were trained on the use of RIS. The students in the experimental group were taught using RIS while the students in the control group were taught using conventional teaching method. Treatment in the two groups lasted for five weeks. The instrument was administered as pre-test and post-test. The data obtained were analysed using mean, standard deviation and analysis of covariance. Findings showed that students in experimental group taught with RIS achieved significantly higher than those in the control group. Also, RIS influenced the achievement of both male and female students. The study recommended that, chemistry teachers should use RIS in teaching and learning of chemistry to male and female students so as to enhance their academic achievement.